Clinical genomic profiling identifies TYK2 mutation and overexpression in patients with neurofibromatosis type 1‐associated malignant peripheral nerve sheath tumors. Issue 7 (22nd November 2016) - Hirbe, Angela C.; Kaushal, Madhurima; Sharma, Mukesh Kumar; Dahiya, Sonika; Pekmezci, Melike; Perry, Arie; Gutmann, David H.
Abstract : BACKGROUND: Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive sarcomas that arise at an estimated frequency of 8% to 13% in individuals with neurofibromatosis type 1 (NF1). Compared with their sporadic counterparts, NF1‐associated MPNSTs (NF1‐MPNSTs) develop in young adults, frequently recur (approximately 50% of cases), and carry a dismal prognosis. As such, most individuals affected with NF1‐MPNSTs die within 5 years of diagnosis, despite surgical resection combined with radiotherapy and chemotherapy. METHODS: Clinical genomic profiling was performed using 1000 ng of DNA from 7 cases of NF1‐MPNST, and bioinformatic analyses were conducted to identify genes with actionable mutations. RESULTS: A total of 3 women and 4 men with NF1‐MPNST were identified (median age, 38 years). Nonsynonymous mutations were discovered in 4 genes (neurofibromatosis type 1 [ NF1 ], ROS proto‐oncogene 1 [ ROS1 ], tumor protein p53 [ TP53 ], and tyrosine kinase 2 [ TYK2 ]), which in addition were mutated in other MPNST cases in this sample set. Consistent with their occurrence in individuals with NF1, all tumors had at least 1 mutation in the NF1 gene. Whereas TP53 gene mutations are frequently observed in other cancers, ROS1 mutations are common in melanoma (15%‐35%), another neural crest‐derived malignancy. In contrast, TYK2 mutations are uncommon in other malignancies (<7%). In the current series, recurrent TYK2 mutations were identified in 2 cases of NF1‐MPNST (30% of cases), whereas TYK2 protein overexpression was observed in 60% of MPNST cases using an independently generated tissue microarray, regardless of NF1 status. CONCLUSIONS: Clinical genomic analysis of the current series of NF1‐MPNST cases found that TYK2 is a new gene mutated in MPNST. Future work will focus on examining the utility of TYK2 expression as a biomarker and therapeutic target for these cancers. Cancer 2017;123:1194–1201. © 2016 American Cancer Society . Abstract : Neurofibromatosis type 1‐associated malignant peripheral nerve sheath tumors are deadly sarcomas with few treatment options. Using clinical‐grade genomic profiling, tyrosine kinase 2 ( TYK2 ) was identified as a new gene that is mutated and overexpressed in malignant peripheral nerve sheath tumors.